Better public sector governance through partnership with the private sector and civil society: the case of Guatemala’s forest administration - Birner, Regina; Wittmer, Heidi (SAGE Publications, 2006)
Improving public sector governance is an important challenge for developing countries. Taking the case of Guatemala’s forest administration, the Instituto Nacional de Bosque (INAB), as an example, this article analyses an innovative option for public sector reform: the delegation of authority to an independent agency that is jointly managed by professionals from the public sector, the private sector and civil society. The article develops an analytical framework, based on transaction cost economics and politics. The analysis shows that delegation and partnership have considerable potential to reduce political interest capture, but they involve potential problems of ‘delegatee drift’ and ‘legitimacy drift’. In view of this trade-off, the comparative advantage of delegation and partnership is influenced by the level of organization among the stakeholders, their managerial capacity and the degree to which they share common interests. The article also discusses the political dimension of the reform process that led to the creation of the INAB.